A Rare Combination of Mixed Germ Cell Tumour of Testis- A Case Report (Anwer Khan Modern Medical College Journal, 2015)
A 20 years old man presented with 4 year history of painless swelling of the left testis. He ignored this swelling until he started having pain in the abdomen. Ultrasonography revealed testicular malignancy with multiple para-aortic lymph nodes enlargements in the abdomen. His X-ray chest showed pulmonary metastasis. One tumor marker was raised. Histology revealed mixed germ cell tumour with a rare combination of seminoma and embryonal carcinoma. Because of this rare combination of 2 varieties of testicular germ cell tumor and extensive systemic metastasis we presented this case. We discussed the epidemiology, incidence, classification, staging, treatment and prognosis of testicular cancer.Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 50-54